Perancangan Sistem Kontrol Suhu Ruangan Server Menggunakan Arduino Uno Di Pusat Komputer Universitas Negeri Manado - Dani Orlando; Daniel Kaparang; Kristofel Santa (JOINTER : Journal of Informatics Engineering, 2021)
Abstract—Microcontrollers are now growing rapidly and are increasingly in demand on system applications control. These days, there are many microcontrollers that already in module form. One of the microcontroller module that is widely used is Arduino. Arduino is a type of board which contains a microcontroller. Combined with the ESP8266-01 module and NodeMCU makes the microcontroller can be connected via internet network. Microcontroller board device Arduino makes it possible to process the temperature reading data from the temperature sensor for support to the display unit using an android based smartphone and controlling AC temperature using Telegram. The processing result data from this Arduino board will be transmitted using wireless media connected to internet network.